2020
DOI: 10.30565/medalanya.636497
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric evaluation of coccyx in patients with coccydynia and classification

Abstract: Amaç: Koksidinalı hastalarda morfolojik ve patolojik anatominin özellikleri sınıflandırmayı amaçladık. Hastalar ve Yöntem: Nisan 2015-Nisan 2018 tarihleri arasında Alanya Alaaddin Keykubat Üniversitesi Eğitim Araştırma Hastanesine koksidina yakınması ile başvuran 16 yaş ve üzerindeki hastalar çalışmaya dahil edildi. Hastaların oturarak ve ayakta çekilen koksiks ve ön-arka pelvis grafileri retrospektif olarak incelendi. Bulgular: Koksiksin skolyozunun, hipermobilitesinin ve dislokasyonunun sakrokoksigeal açılan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…According to this, in the ICA measurement, no statistically significant difference was observed when ICA: 47.9° was taken as a reference in the study by Kim and Suk (p>0.05). [7] In the measurement of SCA, no statistically significant difference was observed according to its value when SCA: 115° was taken as a reference in the study by Özkal et al, [6] (p>0.05).…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations
“…According to this, in the ICA measurement, no statistically significant difference was observed when ICA: 47.9° was taken as a reference in the study by Kim and Suk (p>0.05). [7] In the measurement of SCA, no statistically significant difference was observed according to its value when SCA: 115° was taken as a reference in the study by Özkal et al, [6] (p>0.05).…”
Section: Resultsmentioning
confidence: 85%
“…This appeared to be similar to the measurement previously made in patients with coccydynia. [6] Furthermore, Yoon et al [31] found the mean SCA value of 110° in 606 patients.…”
Section: Meanmentioning
confidence: 99%
See 2 more Smart Citations
“…The treatment of coccygodynia can be difficult and complex due to the variability of anatomy, along with the complexity of the visceral, autonomic, and neuropathic parts. [17] Radiography can be used in diagnosis [18] ; however, an effective diagnostic tool to detect pain in the coccyx is the increase in palpation which is used. [1,3] Initially, conservative management is carried out by prescribing analgesic and anti-inflammatory drugs, and in severe cases, steroid injections are utilized or surgical treatment if issues persist.…”
Section: Introductionmentioning
confidence: 99%